2018
DOI: 10.5539/ijbm.v13n2p76
|View full text |Cite
|
Sign up to set email alerts
|

Grey vs. Young Entrepreneurs: Are They Really That Different in Terms of Entrepreneurial Intentions? Empirical Evidence from Italy

Abstract: In the past, entrepreneurship was considered a young person's endeavour, since it was a working choice made after graduation. Social and demographic changes occurring over the last decades have totally modified that assumption so that entrepreneurship is now a phenomenon involving third age people (aged 55 or older) as well. Scholars have started investigating the differences between young and grey entrepreneurs. This topic of research has always been considered halfway between psychological and social studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…Given that PEs can be 15 or 50 years old, experienced or inexperienced, well connected or unconnected, it made sense for us to embrace the heterogeneity in our study, which our diverse sample of students at multiple levels of different programs offers. Especially given our focus on human capital and recent studies showing little difference in capital effects on entrepreneurial outcomes at different ages (Matricano, 2018), there are still significant differences due to level of education (Matricano, 2020). Our sample is appropriate to test our model and is consistent with other studies on this research topic (Grégoire et al, 2019;Hsu et al, 2017;Shepherd et al, 2019).…”
Section: Limitationssupporting
confidence: 72%
“…Given that PEs can be 15 or 50 years old, experienced or inexperienced, well connected or unconnected, it made sense for us to embrace the heterogeneity in our study, which our diverse sample of students at multiple levels of different programs offers. Especially given our focus on human capital and recent studies showing little difference in capital effects on entrepreneurial outcomes at different ages (Matricano, 2018), there are still significant differences due to level of education (Matricano, 2020). Our sample is appropriate to test our model and is consistent with other studies on this research topic (Grégoire et al, 2019;Hsu et al, 2017;Shepherd et al, 2019).…”
Section: Limitationssupporting
confidence: 72%
“…The main difference is in the perception of having the skills to undertake a venture and they point out that programs aimed at establishing intergenerational skills can positively influence the creation of new ventures. In line with these authors, Matricano (2018) has also identified that the differences are not very significant between young and senior entrepreneurs from the point of view of the use of human capital. Seniors more commonly assign a non-monetary value to their new ventures as it improves their flexibility and their life quality.…”
Section: Literature Reviewsupporting
confidence: 61%
“…As such, these organizations (either public or for profit) are a well-known phenomenon in many countries and especially vivid in the branch of new technologies, where mostly technological start-ups are being sponsored. Thus, most of such initiatives are being targeted at younger persons—the ideal type of an entrepreneur (Matricano, 2018 ). However, some efforts, mostly in Europe, have started to encourage and support senior entrepreneurship.…”
Section: Senior Entrepreneurship Incubators As Models Of Social Innovmentioning
confidence: 99%